2010
DOI: 10.2217/bmm.09.92
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Familial Alzheimer's Disease Gene Mutations with Clinical Phenotype

Abstract: Alzheimer's disease (AD) causes devastating cognitive impairment and an intense research effort is currently devoted to developing improved treatments for it. A minority of cases occur at a particularly young age and are caused by autosomal dominantly inherited genetic mutations. Although rare, familial AD provides unique opportunities to gain insights into the cascade of pathological events and how they relate to clinical manifestations. The phenotype of familial AD is highly variable and, although it shares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
140
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(147 citation statements)
references
References 79 publications
(94 reference statements)
4
140
0
3
Order By: Relevance
“…Mutaciones en el cromosoma 1, como las Y231C, M239V y T122R 24 , son causales de EA, y los afectados pueden presentar un cuadro demencial en el que se hay alteraciones neuroconductuales y parkinsonismo, al igual que en las mutaciones PS2A85V y A85V 25 .…”
Section: Enfermedad De Alzheimer Familiar Precozunclassified
See 1 more Smart Citation
“…Mutaciones en el cromosoma 1, como las Y231C, M239V y T122R 24 , son causales de EA, y los afectados pueden presentar un cuadro demencial en el que se hay alteraciones neuroconductuales y parkinsonismo, al igual que en las mutaciones PS2A85V y A85V 25 .…”
Section: Enfermedad De Alzheimer Familiar Precozunclassified
“…Sumado a los trastornos cognitivos, es frecuente encontrar alteraciones neuroconductuales y parkinsonismo 24 .…”
Section: Descripción Fenotípicaunclassified
“…Clinical studies indicated that many patients with FAD mutations in PS1 display significant phenotypic heterogeneity, including variable age of onset, penetrance, myoclonus and seizures, Parkinsonism, apraxia/ataxia, FTD and psychiatric symptoms [73][74][75]. There are also variations in PS1-FAD neuropathology.…”
Section: Er Ca 2+ Leak and Variant Admentioning
confidence: 99%
“…There are also variations in PS1-FAD neuropathology. For instance, greater NFT formation, altered amyloid β plaque composition, hippocampal sclerosis, the appearance of Pick bodies and neuropathological involvement of the basal ganglia and/or brainstem [73][74][75]. An intriguing subset of PS1-FAD patients manifest symptoms of spastic paraparesis (SP, known as variant AD), or progressive spasticity of the lower limbs [73][74][75][76].…”
Section: Er Ca 2+ Leak and Variant Admentioning
confidence: 99%
See 1 more Smart Citation